Diarrhoea management practices and child health outcomes in Nigeria: Sub-national analysis. - Akinyemi, Akanni Ibukun; Fagbamigbe, Adeniyi F.; Omoluabi, Elizabeth; Agunbiade, Ojo Melvin; Adebayo, Samuel Olanipekun (Advances in Integrative Medicine, 2018)
Introduction This paper examined the management of diarrhoea at sub-national levels with the aim of providing an analytic view towards linking diarrhoea management to sources of care within the Nigeria context. Methods We used the 2013 NDHS data. Based on the 2004 WHO/UNICEF guidelines, we classified the quality of diarrhoea management practice as good, fair or poor. Having ‘Good’ diarrhoea management is our dependent variable. Descriptive statistics, Chi-square statistics, logistic regression models and life table techniques were used to analyse the data. All analyses were carried out using Stata version 13, weighted and adjusted for survey design and sampling errors at 5% significance level. Results The overall prevalence of diarrhoea was 9% with 6% among 0–6 months old children and 16% among those aged 7–23 months. Diarrhoea prevalence was highest in the North-East region of Nigeria (16%). Prevalence was 10% among children whose mothers had no education and 11% among children from the poorest households. Quality of diarrhoea management was significantly associated with child’s age, mother’s age, wealth quintile, place where treatments were taken, health care accessibility, parental education, having blood in stool, quality of water and open defecation. Children who had care from the hospital were over 8 times more likely to experience good diarrhoea management compared with other children who didn’t receive care from hospitals (OR = 8.18, 95% CI: 5.73–11.69). Furthermore, children from urban areas (OR = 2.03, 95% CI: 1.58–2.60) or whose mother reported access to modern health care services (OR = 2.23, 95% CI: 1.72–2.88) were more likely to experience good diarrhoea management. Child survival increased with higher levels of good diarrhoea management. Conclusion In Nigeria, treatment of childhood diarrhoea at home and in the community is not as effective as that obtained from the health facility.